The effects of language barriers towards job performance and job satisfaction among employees at multilingual organisations / Nur Syahira Md Subre - Md Subre, Nur Syahira (2024)
English is a commonly utilised language for communication in the contemporary global economy, where more and more business is done on a global basis. Speaking and writing in English at multilingual workplace can boost client and employee relationships internationally, increase one's skill level and ability to command a higher salary internationally, and promote cross-cultural interactions. However, any linguistic constraint at workplace that causes misunderstanding or restricts comprehension is considered a language barrier. National or cultural languages might be a barrier, but it might also be specialised knowledge or speech issues. One of the potential communication problems in multilingual workplace is language barriers, particularly when there are multiple languages spoken by the employees. This study purposely conducted to identify the most frequent language barriers, the level of language competency, level of job performance and level of job satisfaction among employees in a multilingual workplace. This study also determine the moderating impact of education background between language barriers with job performance and job satisfaction. Education background is one of the components highlighted in demographic profile. Past studies shown that education background plays a vital role in organisational communication. Hence, in this study, education background had been selected as a moderating variable. In addition, this study used quantitative approach and questionnaires as research instrument. There are 363 respondents had been selected in this study using Krejcie and Morgan formula. Respondents involved in this study are the employees who work in tourism industry. Questionnaires had been distributed to the respondents and data obtained. Results in this study shown that most of the respondents have low level of language competency, low level of job performance and low level of job satisfaction.